Erte - Ryan, Tony.; Seven Arts, Ltd. (s.l. Master Vision)
A portrait of the life and work of Roman de Tirtoff, better known as Erte, the artist who contributed greatly to the development and acceptance of art deco, a design movement of the 20th century.
Title on cassette : Degas, Erte, Chagali.
Keywords: Erte; Costume designers -- Biography. -- France